2001
DOI: 10.1097/00005392-200109000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Tibial Nerve Stimulation as Neuromodulative Treatment of Lower Urinary Tract Dysfunction

Abstract: Posterior tibial nerve stimulation is a minimally invasive and successful treatment option for patients with certain types of lower urinary tract dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 17 publications
2
47
0
4
Order By: Relevance
“…Some articles included patients who also appear in other PTNS articles. In particular, our review identified a series of six interrelated articles, which share common authors and common study elements [19,38,47,49,50,53]. As a result, it was not possible to definitively determine the total number of subjects enrolled in the complete body of 16 PTNS articles included in our review.…”
Section: Implanted Sacral Nerve Stimulationmentioning
confidence: 99%
“…Some articles included patients who also appear in other PTNS articles. In particular, our review identified a series of six interrelated articles, which share common authors and common study elements [19,38,47,49,50,53]. As a result, it was not possible to definitively determine the total number of subjects enrolled in the complete body of 16 PTNS articles included in our review.…”
Section: Implanted Sacral Nerve Stimulationmentioning
confidence: 99%
“…Sie basiert ebenso wie die sakrale Neuromodulation auf der Stimulation der Blase und Beckenboden versorgenden Nerven, ist jedoch nicht invasiv und hat praktisch keine beschriebenen Nebenwirkungen [7,10,13,15].Unsere Untersuchung sollte den klinischen Stellenwert dieser Methode bei Patienten mit nichtneurogener Blasenfunktionsstörung prüfen.…”
Section: Erste Ergebnisse Der Peripheren Neuromodulation Nach Stollerunclassified
“…Eine erfolgreiche Therapie wurde über den Wunsch des Patienten, die Stimulation fortzusetzen, definiert. Bei den Patienten mit nichtobstruktivem chronischem Harnverhalt wurden weder bei der Anzahl der Katheterisierungen pro Tag noch bei Miktionsvolumen oder Restharn signifikante Verbesserungen erreicht [15]. Die Arbeitsgruppe um Klingler behandelte 15 Patienten mit überaktiver Blase und pelvic pain.…”
Section: Introductionunclassified
“…In the literature, there are several studies evaluating the benefits of PTNS on overactive bladder symptoms and quality of life [13,14]. PTNS has been effective in patients that did not respond to anticholinergic treatment [15].…”
Section: Introductionmentioning
confidence: 99%